S-D614G Mutation Reveals the Euro-America and East-Asia Origin SARS-CoV-2 Virus Spread in Indonesia - Anggraini, Nina Bunga; Listyorini, Dwi (Jurnal Riset Biologi dan Aplikasinya, 2021)
COVID-19 is a pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. The first case was found in the city of Wuhan, Hubei province, China. The first case in Indonesia was reported in March 2020 and currently there are 0.5 million cases with a death rate of 3.1%. This rapid increase in cases is thought to due to presence of the mutant strain S-D614G, which causes a faster rate of infection and spread. The purpose of this study was to determine the presence of S-D614G mutations in Indonesian samples in order to find the origin of COVID-19 which was spread in Indonesia based on the Spike gene sequences and the RdRp genes from 25 countries, and one control sequence China/Wuhan-Hu-1 obtained from the NCBI and GISAID databases. Mutation analysis was carried out through multiple alignments using BioEdit software. Phylogenetic tree reconstruction using MEGA6 software with the Neighbor Joining method. This study found mutation of S-D614G in one Indonesian sample, namely the Indonesian/SBY9 sample along with 23 samples from Europe, America, and Africa. The phylogenetic tree reconstruction confirmed these findings; the mutated samples were closely related to samples from these continents, while the non-mutated Indonesian samples were closely related to sample from East Asia. These findings indicate that the origin of the SARS-CoV-2 virus in Indonesia possibly came from the East Asia cluster and the European-American cluster.